Geographical Preconditions and Factors of the Russia-Ukraine Conflict - Mozghovyi, A. A. (Ukrainian Geographical Journal, 2024)
The article examines the geographical prerequisites and factors contributing to the long-term Russia-Ukraine conflict. The Russia-Ukraine confrontation has been going on in Eastern Europe for several hundred years and has now acquired the existential character of a genocidal war. The modern Russia-Ukraine war, which began in 2014, is considered in this study as one of the stages of a long and multi-level confrontation. In the author’s opinion, this long-running conflict is close to the point of the most complete involvement of resources by the parties to the conflict, that is, maximum escalation. This study aims to determine the role of geographical factors in the Russia-Ukraine conflict. The primary objective of this geoconflictological study is to examine the impact of geographical prerequisites and factors on the progression of the long-term and multi-level Russia-Ukraine conflict. In particular, it was established that the deep contradictions underlying this conflict were laid down at the pre-conflict stage. The geographical location of the subjects in the Russia-Ukraine conflict also plays a role. The author emphasizes the significant importance of distance in Russia-Ukraine relations. In particular, the role of these factors in creating the contradictions that formed the subject of this long-term and multi-level conflict is determined. The influence of geospatial, historical-geographical, and political-geographical factors on the overall course of this conflict is analyzed. This article, for the first time, defines the role and significance of geographical prerequisites and factors in the Russia-Ukraine conflict from the research standpoint of geoconflictology.